The Impacts of Social Media Marketing Towards Purchase Intention on Beauty E-Commerce in Jakarta - Maulida Rahma Nabila; Usep Suhud; Rahmi Rahmi (IQTISHADequity jurnal MANAJEMEN, 2023)
This study examines how social media marketing affects purchase intentions for beauty products through e-commerce in Jakarta. The study focuses on various social media marketing factors such as brand awareness, brand image, brand trust, and purchase intention. The study sample was individuals aged 16-30 years residing in Jakarta who have bought or have intention to purchase makeup or skincare products through beauty e-commerce. Data were analyzed using exploratory and confirmatory factor analyses to validate data and structural equation model to test hypotheses. The study's hypotheses revealed that social media marketing significantly influences brand awareness, brand image, and brand trust. However, brand awareness had no significant influence on purchase intention. Nevertheless, the study found that brand awareness significantly influences brand image, which, in turn, positively affects purchase intention and brand trust. Conversely, brand trust had no significant influence on purchase intention.